Development of database management system (DBMS) based on elemental cost analysis (ECA) methodology - Berahim @ Ibrahim, Siti Khairizan (2006)
For 30 years, major Quantity Surveying (QS) consultants from the developed country have started to produce the Database Management System (DBMS) for estimating process. Development and installation of the software required high expenses. These conditions encourage the development of estimating software in the market. Currently, there are few estimating software in the market. These systems are difficult to use because they are not developed by the practicing QS themselves and not comprehensive enough. Therefore, this study aims to develop a software based estimating system using Elemental Cost Analysis (ECA) method. Extensive study was performed at the initial stage of this study using various methodologies such as interviews, questionnaire survey, and case studies in order to identify the viability of the developed system. This study found that the developed systems which integrate the application of DBMS system and ECA method increases efficiency and speed of estimating system. The developed system has been tested on real project and verified by a panel of experts. The results of the validation process encourage the recommendation of the developed system for practical implementation in the industry.